Pengaruh Aksesibilitas dan Tingkat Pengungkapan Laporan Keuangan terhadap Akuntabilitas Keuangan Daerah - S, Sukhemi (Akmenika, 2013)
The research aims at analyzing the impact of accessibility and the range of explana-tion in finance report towards the accountability of district finance. This research used double linear regression model.In collecting data, this empirical research used quota sampling technique. The data are collected by using 200 questionnaires that spread to many stakeholders of district finance report such as legislators, public servant, lecture, and labors. Data was ana-lyzed by using double linear regression with program SPSS version 16.The research result shown that accessibility positively influence toward accounta-bility in district finance. The range of explanation in finance report have not influence significantly toward accountability in district finance.